The Mediating Role of Overall Equipment Effectiveness on the Relationship between Fit Manufacturing and Business Performance - Ibrahim Esmaeel, Raghed; Zakuan, Norhayati; Mohd Jamal, Noriza (International Journal of Engineering and Technology, 2018)
Advanced manufacturing technology systems have replaced traditional manufacturing systems as manufacturing industry have many technological developments in recent years. Now, the primarily concern is effectiveness of the equipment for the modern manufacturing technology systems. Though, there is a lack of empirical studies confirming this impact on business performance. Recently, manufacturing industries have adapted fit manufacturing strategies in order to enhance the system effectiveness to get competitive advantage. These strategies are mainly, lean, agile and sustainable manufacturing. This paper aims to systematically review the literature on the existing fit manufacturing strategies and their relationship with business performance from year 2009 to 2015, also to find the possible intervening variable that can influence the inconsistency of the relationships between the fit manufacturing strategies and business performance. On the basis of the findings from the systematic literature review, we suggest researchers on the in the field of operations management to investigate the mediating relationship of overall equipment effectiveness between the relationship of the fit manufacturing strategies and business performance.Â Â